Altered high-density lipoprotein particle structure and antioxidant capacity in preeclampsia - Banjac, Gorica; Ardalić, Daniela; Cabunac, Petar; Ivanišević, Jasmina; Vekić, Jelena; Miković, Željko; Stefanović, Aleksandra (Vojnosanitetski pregled, 2023)
Background/Aim. One of the complications that can occur during pregnancy is the development of preeclampsia (PE). The main characteristics of this condition are high blood pressure and very often signs of kidney damage or other organ damage. The condition affects 5–7% of all pregnant women and is one of the main factors of maternal and perinatal morbidity and mortality worldwide. The aim of this study was to investigate the structural and functional modifications of high-density lipoprotein (HDL) particles during high-risk pregnancies (HRP) for PE development. Methods. The longitudinal prospective study included a total of 91 pregnant women with a HRP for developing PE. Out of this total number, 71 women did not develop PE until delivery, and this group was designated as the group without PE (WPE). The rest of the 20 HRP women developed PE before delivery and were designated as the PE group. The blood was sampled toward the end of each trimester and before the delivery. The distribution of HDL particles was determined by the vertical 3–31% polyacrylamide gradient gel electrophoresis method. The antioxidative capacity of HDL particles was measured by the activity of the HDL-associated enzyme – paraoxonase 1 (PON1). PON1 activity was determined by the method of kinetic spectrophotometry from serum samples. Results. The results have shown that the proportions of HDL2b particles signiﬁcantly increased in the 2nd trimester (p ˂ 0.05) and remained increased until the end of pregnancy in the WPE group. PON1 activity was significantly higher in the 3rd trimester (p < 0.05) of the WPE group. In the PE group, we found that the proportions of HDL3a particles significantly decreased in the 2nd trimester (p < 0.05) and remained decreased until the end of pregnancy. PON1 activity has not changed in the PE group during pregnancy. Conclusion. Dyslipidemia in pregnancy could be associated with different modifications of HDL particles. The adaptive pregnancy mechanisms expressed as a functional modification of HDL particles in pregnant women who develop PE seem inadequate and, therefore, lose their atheroprotective role.